Comparison of the interactions of daunorubicin in a free form and attached to single-walled carbon nanotubes with model lipid membranes - Matyszewska, Dorota (Beilstein Journal of Nanotechnology, 2016)
In this work the interactions of an anticancer drug daunorubicin (DNR) with model thiolipid layers composed of 1,2-dipalmitoyl-sn-glycero-3-phosphothioethanol (DPPTE) were investigated using Langmuir technique. The results obtained for a free drug were compared with the results recorded for DNR attached to SWCNTs as potential drug carrier. Langmuir studies of mixed DPPTE–SWCNTs-DNR monolayers showed that even at the highest investigated content of the nanotubes in the monolayer, the changes in the properties of DPPTE model membranes were not as significant as in case of the incorporation of a free drug, which resulted in a significant increase in the area per molecule and fluidization of the thiolipid layer. The presence of SWCNTs-DNR in the DPPTE monolayer at the air–water interface did not change the organization of the lipid molecules to such extent as the free drug, which may be explained by different types of interactions playing crucial role in these two types of systems. In the case of the interactions of free DNR the electrostatic attraction between positively charged drug and negatively charged DPPTE monolayer play the most important role, while in the case of SWCNTs-DNR adducts the hydrophobic interactions between nanotubes and acyl chains of the lipid seem to be prevailing. Electrochemical studies performed for supported model membranes containing the drug delivered in the two investigated forms revealed that the surface concentration of the drug-nanotube adduct in supported monolayers is comparable to the reported surface concentration of the free DNR incorporated into DPPTE monolayers on gold electrodes. Therefore, it may be concluded that the application of carbon nanotubes as potential DNR carrier allows for the incorporation of comparable amount of the drug into model membranes with simultaneous decrease in the negative changes in the membrane structure and organization, which is an important aspect in terms of side effects of the drug.
Keywords: daunorubicin (DNR); 1,2-dipalmitoyl-sn-glycero-3-phosphothioethanol (DPPTE); drug carriers; model lipid membranes; single-walled carbon nanotubes (SWCNTs)